5(x-2)+3=-2

Simple and best practice solution for 5(x-2)+3=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-2)+3=-2 equation:


Simplifying
5(x + -2) + 3 = -2

Reorder the terms:
5(-2 + x) + 3 = -2
(-2 * 5 + x * 5) + 3 = -2
(-10 + 5x) + 3 = -2

Reorder the terms:
-10 + 3 + 5x = -2

Combine like terms: -10 + 3 = -7
-7 + 5x = -2

Solving
-7 + 5x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 5x = -2 + 7

Combine like terms: -7 + 7 = 0
0 + 5x = -2 + 7
5x = -2 + 7

Combine like terms: -2 + 7 = 5
5x = 5

Divide each side by '5'.
x = 1

Simplifying
x = 1

See similar equations:

| 14x-(3+7x)= | | a/5=-17 | | 14-w/8=3w-21 | | 17/6+(-2/3) | | 4d-3=2(d-3) | | 2cos^2x=sinx+1 | | x+2x-48=-6 | | 2a^3b(3a^2b+ab^2)= | | m^3+2m^2+9m+18=0 | | 6(5x-5)-5(4x-15)=3(3x+4)-1 | | -2.6x-3.52=-17.3 | | 0.4x+3.4=5.78 | | 2y-7=x | | 12.3-0.6p+1.5-1.5p=8-2.1p-6.6 | | -16t^2+400= | | -2a+12+8a=5a-3a | | 179/16-61/12 | | 3(2-s)=9 | | 31/3+x=53/4 | | 17+2n+3n-9=14n+15-9n-7 | | x+2x-63=0 | | 2(x-1)+1=9 | | 15x^2+2x-1=0factoring | | -2x-4(2x-8)=-18 | | 1.2(y+5)-(7.8+0.2y)=-5+3 | | 3(2x-2)+6=-12 | | 6=3-4x-5 | | 6z-10-z+5=0 | | 25/6-25/8 | | 3ab(2a^2+3b^3)= | | 8+32n=31+17 | | 0=4x+6-3x+2 |

Equations solver categories